Keluarga Katolik, Mea Dan Sekularitas - Hironimus Bandur (Jurnal Alternatif Wacana Ilmiah Interkultural, 2017)
Indonesia may be called a multi-religious country. Nevertheless, the State of Indonesia is not a State which makes religion its basis. The basis of the State of Indonesia is Pancasila and the issue of religion is placed as the number one issue in the order of Pancasila. With the above statement, it clearly affirms that the State of Indonesia is not at once a secular state or a State of religion. Likewise in all aspects of his life including family. But there is no denying the fact that the State and on the micro scale, the family has been much influenced by the flow of secularization. Today, there is also an economic awareness of the people of ASEAN region and finally forming a container called MEA (ASEAN Economic Community). This stream will in turn overwhelm the Catholic family and even urge the family to take part in the MEA flows. This context can shake the family order, including the Catholic family. Therefore, Catholic families must continue to be empowered through the radiance of the Eucharistic meaning. The family should always be reminded that the Eucharist is the culmination and source of the Christian faith. Catholic families must remain Eucharistic families